Pełzanie Wiotkich Obrotowo-Symetrycznych Powłok Niesprężystych w Zakresie Skończonych Odkształceń - Wilk, J. (Engineering Transactions, 1970)
Presented here are numerical methods of solving system od differential Eqs. (2.4), (3.6), and (4.4), derived on the basis of various physical relations (the theory of ageing, steady and unsteady flow), describing the form state of stresses and deformations in the process of creeping of frail rotationally-symmetrical shells in the range of large deformations. On the basis of the block schemes included in the paper, universal programmes were made for the electronic computer Odra-1013, by means of which concrete solutions were obtained for the case of a cylindrical shell loaded with a constant internal pressure. The results of the calculations illustrate the behaviour of the shells, with special reference to the problem of stability solved according to different theories of creeping.